Professional Entrepreneurial Competencies and Creativity Skills Formation Under the Influence of Educational Practices of Start-Up Projects Development - Mutalimov, Verdi; Volkovitckaia, Galina; Buymov, Arkady; Syzdykov, Shalkar; Stepanova, Diana (Journal of Technical Education and Training, 2021)
This article defines the role of start-up projects as a pedagogical tool aimed at consolidating and updating vocational training of students majoring in entrepreneurial studies. It presents an online survey conducted among Russian and Azerbaijan entrepreneurs, which allowed identifying key competencies necessary to practice a flourishing business activity in the current environment. The role of start-ups in strengthening and upgrading entrepreneurship studentsâ€™ professional competencies was identified based on self-assessment of their professional progress during educational training. The research methodology made it possible to identify levers of influence on studentsâ€™ involvement in training, the effective usage of which can dramatically change the quality of future specialistsâ€™ education due to the synergy of theoretical and practical activities. Using a survey of 50 Russian and Azerbaijani entrepreneurs, selected using a series of filters and based on a random sample, a list of entrepreneurs’ competencies and skills was formed. Checking by the Cronbach method a demonstrated the acceptability of the internal reliability of the resulting list (Î± = .821). This list was used to survey 395 students from 5 Russian and one Azerbaijani universities using the method of assessing on a 4-point Likert scale their results in entrepreneurship training after The practical vocational training in the â€œStart-up Projects - New Generationâ€ ecosystem, described in this study. The students’ assessment of the level of development of their vocational skills turned out to be relevantly high. In practice, the research results can be applied in the creation of entrepreneurship training courses, as well as with the aim of increasing student entrepreneurship motivation and enhancing their practical experience.